Дослідження реологічних властивостей суспензій пірогенного кремнезему, модифікованого полідиметилсилоксаном, у вазеліновій олії - Goncharuk, O. V.; Sulym, I. Ya. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
The effect of the surface modification of fumed silica (SiO2) with poly(dimethylsiloxane) (PDMS) on the rheological properties of its suspensions in vaseline oil has been studied in the current work. The composites with different polymer content (from 5 to 40 wt. %) were synthesized by using the method of liquid phase adsorption modification of silica with linear PDMS-1000 (molecular weight Wm ? 7960, degree of polymerization dp = 105). It is shown that the structural and morphological characteristics of SiO2/PDMS composites are significantly different from those for the initial silica, and depend on the concentration of PDMS. In particular, the specific surface area of the composites, determined by the method of low-temperature desorption of argon, is inversely correlated with the content of polymer. The morphology of SiO2/PDMS composites and aggregation of primary particles of fumed silica strongly depends on the method of liquid phase adsorption modification: the initial fumed SiO2 has a wider distribution of aggregates in size than that in polymer composites according to AFM data. Suspensions with a solid phase concentration (SiO2/PDMS) of 5 wt. % in a lyophilic dispersion medium (vaseline oil) demonstrate typical thixotropic behavior with a characteristic hysteresis loop on the rheogram, corresponding to increasing the destruction of the dispersion structure while stepwise shear rate increment and partial its restoration while subsequent stepwise shear rate decrement. Both the effective viscosity values corresponding to the maximum destruction of the suspension structure obtained at high shear rates and the effective viscosity values corresponding to partial restoration of the structure in the subsequent stepwise shear rate decrement mode decrease with increasing polymer content in the studied composites. However, it has been found that the initial values of the effective viscosity for the studied dispersions with a practically almost intact structure (at the lowest shear rates) are higher for dispersions of SiO2/PDMS composites with a low concentration of PDMS 10–20 wt. % compared with similar suspensions of the initial silica. A correlation between the effective viscosity and the specific surface area of composites is shown.